Clinical management of pregnant women with the risk of pre-eclampsia developing. - T. O. Loskutova (Medičnì Perspektivi)
Hypertensive disorders in pregnancy remain important problem of modern obstetrics, their frequency being 2-8% with no tendency of decreasing. To identify pregnant women with high risk and to conduct preventive treatment is very important for the practitioner. The aim of the study was to develop and justify differential management of pregnants depending on the risk of preeclampsia. 131 pregnant women in I trimester were tested to determine the risk of hypertensive disorders. Prediction model allows to identify pregnant women with risk of hypertensive disorders according to the results of testing thrombophilia genes (presence of 455G → A polymorphism in the gene for fibrinogen β and 4G/5G in gene of plasminogen activator inhibitor - type 1), the level of antibodies to β2 glycoprotein-1, the level of D-dimer and the value of atherogenicity coefficient. Pregnant women with high risk of hypertensive disorders, received prophylactic treatment complex. This complex included antiplatelet therapy, correction of hyperhomocysteinemia and hypercholesterolemia levels. Etio-pathogenic concept of prediction and prevention of pre-eclampsia associated with thrombophilia was proposed. The proposed scheme of preventive treatment allowed to normalize blood clotting parameters, lipid metabolism, to reduce the number of thrombophilia markers. The necessity of early and long-term administration of prophylactic complex was proved. This management prevents endothelial damage and development of pathological range of pre-eclampsia. The results of prophylactic treatment were the reduction of preeclampsia cases by 6,5 times (p < 0.05), number of complicated deliveries by 3 times (p <0.05), number of preterm birth by 6,57 times (p <0.05), cases of growth retardation by 9,8 times (p = 0.003), increase of newborns’ weight by 1,24 times (p = 0.02).